Answer:
The answer is 432
Step-by-step explanation:
6 x 8 x 9 =432
Use Pythagorean theorem:
9i-j = sqrt (9^2 - 1^2) = sqrt(81-1) = sqrt80
now divide both terms in V by that:
u = 9/sqrt(80)i - 1/sqrt(80)j
see attached picture:
Answer:
(x + 3)^2 + (y - 2)^2 = 9
Step-by-step explanation:
<u>Equation for a circle: (x – h)^2 + (y – k)^2 = r^2</u>
<u />
<u>Step 1: Determine what h, k, and r are</u>
<em>h is the x value of the point: -3</em>
<em>k is the y value of the point: 2</em>
<em>r is the radius of the circle: 3</em>
<u>Step 2: Plug in and solve</u>
(x – h)^2 + (y – k)^2 = r^2
(x – (-3))^2 + (y – (2))^2 = (3)^2
<em>(x + 3)^2 + (y - 2)^2 = 9</em>
<em />
Answer: (x + 3)^2 + (y - 2)^2 = 9
7+8= 15 so the second answer
Answer:
457
Step-by-step explanation: